Effect of sorghum type and harvest date on silage feeding value - Smith, R.; Bolsen, K.; Ilg, H.; Hinds, M.; Dickerson, J.; Hoover, J.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Five silages produced in 1982 were evaluated in two growing trials using 96 steer calves. Forage sorghum silage (heading) was assigned a feeding value of 100. Based on comparative rates and efficiencies of gain, feeding value for the grain sorghum silage averaged 107.5 in Trial 1. The non-heading forage sorghum silage had a value of 64.6 in Trial 1 but only 40.2 before freezing and 31.4 after freezing in Trial 2. The poor values for the non-heading silages were due, in part, to very low feed intakes. There was no advantage in harvesting the non-heading sorghum after a freeze. Rolling the grain sorghum silage to break 95 % of the grain did not improve its value. In Trial 2, adding alfalfa haylage to the non-heading silages did increase steer performance.
Keywords: Beef; Sorghum; Harvest; Silage; Value